The impact of sea ice on the initiation of the spring bloom on the Newfoundland and Labrador Shelves - Wu, Yongsheng; Peterson, Ingrid K.; Tang, Charles C. L.; Platt, Trevor; Sathyendranath, Shubha; Fuentes-Yaco, César (Journal of Plankton Research, 2007)
The relationship between sea ice and the phytoplankton spring bloom over the Newfoundland and Labrador shelves is examined using remotely-sensed chlorophyll data and sea-ice data for the period 1998–2004. A regression analysis between the two data sets shows that the retreat of sea ice precedes the spring bloom, and the inter-annual variation of the spring bloom is closely correlated with the start time of ice retreat. The spring bloom off Canada's east coast usually starts on the eastern Grand Banks. Here, the water properties are strongly influenced by sea ice on the Newfoundland shelves in early spring when accelerated ice melting causes the ice edge to retreat north and the melt water is advected south by the Labrador Current. After the ice retreat, the water on the eastern Grand Banks is rapidly stratified and the mixed layer shallows as a result of surface freshening. The shallow mixed layer promotes phytoplankton growth. The regression analysis also reveals that an early spring bloom or ice retreat tends to prolong the duration of the spring bloom.